La migración de los padres y su incidencia en el comportamiento y rendimiento escolar de sus hijos, estudiantes del octavo año de educación básica del Colegio Fiscal Técnico Nacional Carmen Mora de Encalada de la ciudad de Pasaje, periodo lectivo 2012-2013. - Ayala Liendres, Katherine Anabell (2013)
This research focused on the emigration of parents and their impact on behavior and academic performance of students in the eighth year of basic education, school Attorney technical National Carmen Mora de Encalada, city of passage, problematic context that raises in the educational process and social interaction, for which we proceeded to both textual research and bonnet to address the issue. On the other hand, for the operationalization of research related to the qualitative approach -quantitative methods were used. The research was descriptive-explanatory survey were also applied to interviews with students and teachers who work in this year, information provided verification of hypotheses. They were processed and analyzed the data obtained, which allowed to know the reality of the object of research results used in the proposed proposal. the conclusions and recommendations were also determined, which justified the investigative process.